Pemikiran Gender Fatima Mernissi Terhadap Peran Perempuan - Ratna Wijayanti; Hendri Hermawan Adinugraha; Mila Sartika; Ahmad Anas (MUWAZAH : jurnal kajian gender, 2018)
The research is to know and examine the thoughts of Fatima Mernissi about the role of women and how the critics of Fatima Mernissi thought. The research method used literature research where the data obtained from literatures related to Fatima Mernissi thinking about the role of women in Islam. The result of this research is that Fatima Mernissi tried to reconstruct thinking about the role of Fatima woman by exploring the values and teachings in al-Qur’an that affirm equality of men and women. Fatima Mernissi quotes several verses of the Qur’an, which assert that the vision and mission of Islam uphold and provide absolute certainty related to sexual equality. The moment of migration of a political action involving men and women, should be interpreted as an affirmation and justification of Islam for public participation of women in the social and political sphere.